The price we pay economic and social consequences of inadequate education - Belfield, C. R.; Levin, Henry M. (Brookings Institution Press, 2007)
"Highlights costs of inadequate education, attaching hard numbers to the relationship between educational attainment and critical indicators as income, health, crime, dependence on public assistance, and political participation. Explores policy interventions to boost the education system's performance and explains why demographic trends are so challenging to educating the nation's youth"--Provided by publisher.